1999
DOI: 10.3168/jds.s0022-0302(99)75523-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and Metabolic Responses to Graded Abomasal Doses of Methionine and Lysine in Cows Fed Grass Silage Diets

Abstract: Five rumen-cannulated Finnish Ayrshire cows were used in two 5 x 5 Latin square experiments designed to study the lactation and metabolic responses to increasing doses of DL-Met or L-Lys infused into the abomasum. The cows were fed grass silage ensiled with a formic acid additive for ad libitum intake. A supplement with barley and oats was given at a rate of 9 kg/d (Experiment 1) or 7 kg/d (Experiment 2). The experimental treatments were 0, 10, 20, 30, or 40 g of Met/d (Experiment 1) and 0, 15, 30, 45, or 60 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
54
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 23 publications
14
54
1
3
Order By: Relevance
“…However, it may be speculated that milk fat secretion was increased as a result of increased supply to both the mammary gland (e.g., in the low-CP LM diet) and liver (e.g., high-CP LM diet). Similar results were observed when plasma Met concentration was increased during abomasal infusion of LM or LM plus His in dairy cows fed grass-silage-based diets Varvikko et al, 1999). Lys uptake and balance ratios were higher in the low-CP compared to high-CP diets regardless of the LM infusion without any alteration in protein secretion.…”
Section: Discussionsupporting
confidence: 77%
“…However, it may be speculated that milk fat secretion was increased as a result of increased supply to both the mammary gland (e.g., in the low-CP LM diet) and liver (e.g., high-CP LM diet). Similar results were observed when plasma Met concentration was increased during abomasal infusion of LM or LM plus His in dairy cows fed grass-silage-based diets Varvikko et al, 1999). Lys uptake and balance ratios were higher in the low-CP compared to high-CP diets regardless of the LM infusion without any alteration in protein secretion.…”
Section: Discussionsupporting
confidence: 77%
“…ferent experiments increased milk protein yields by 50 g d -1 , on average, and fat yields were often elevated, up to 100 g d -1 (Robinson 1996). Varvikko et al (1999) found that Met infused up to 40 g d -1 into the abomasum of cows had no effect on either milk protein yield or percentage, but fat percentage increased linearly with Met dose (Table 1). These results indicate the mechanism of the increase in milk fat is distinct from the mechanism of the increase in milk protein.…”
Section: Addition Experimentsmentioning
confidence: 91%
“…Responses to added Met and Lys, which may include an increase in milk fat yield (Robinson 1996;Varvikko et al 1999), are not always consistent with the correction of an AA deficiency.…”
Section: Subtraction Experimentsmentioning
confidence: 99%
“…Although non-significant (P > 0.1), decreased concentrations of Val, Met and Phe were also noted in our experiment. This discrepancy in response in plasma AA concentrations to Leu infusions is probably caused by the basal diet that seems to be the main factor in determining AA supply, as documented by various responses to Leu supplementation on grass silage or maize silage based diets (Schwab et al, 1992a,b;Vanhatalo et al, 1999;Varvikko et al, 1999;Rulquin and Pisulewski, 2006;Křížová et al, 2008). Further, according to Kröber et al (2001) alterations in blood plasma levels of other AA would reflect interactions with the supplemented AA which, in the case of antagonism, could indicate the necessity of supplementing not only the primarily limiting AA but also others.…”
Section: Blood Parameters and Plasma Aamentioning
confidence: 99%
“…Thus leucine (Leu), which is suggested to be the most-limiting from branched chain AA (e.g. Varvikko et al, 1999), has recently received some attention (Miettinen and Huhtanen, 1997;Varvikko et al, 1999;Iburg and Lebzien, 2000;Rulquin and Pisulewski, 2006) as a potentially limiting AA for milk protein synthesis.…”
mentioning
confidence: 99%